Cadaveric donor factor variations during a 12-year period: influence on kidney transplant outcomes - Nunes, P (2006)
Our purpose was to evaluate changes in cadaveric donor factors between 1993 and 2004 and their impact on the short- and long-term outcomes of renal transplants in a single center. PATIENTS AND METHODS: Cadaveric renal transplants performed in our unit between 1993 and 2004 were divided in two groups of identical length: A (n = 455; 1993-1998) and B (n = 465; 1999-2004). Major differences related to donor, graft, and recipient factors were analyzed between groups and correlated with main outcome parameters. Recipient age, gender, weight, etiology of end-stage renal disease, average length of dialysis, and cold ischemia were not different in the two periods. RESULTS: Grafts harvested in our hospital were more frequent in group A (92.3 vs 78.2%; P < .005). Traumatic causes of death were more frequent before 1999: 90.9 vs 70.9% (P < .001). Mean donor age was higher after 1999: 31.37 vs 35.94 years (P < .005). Female donors were more frequent in the second period: 20.5 vs 26.6% (P < .05). Mean donor weight was also higher: 52.36 vs 67.86 kg (P < .05). All of these differences were unfavourable characteristics regarding graft outcomes. Delayed graft function (A = 13%, B = 24.2%), acute rejection episodes (A = 41.2%, B = 28%), and chronic allograft dysfunction (A = 23.5%, B = 14.4%) were also significantly different between the two cohorts (P < .005). Graft function (serum creatinine at 1 and 2 years), patient and graft survivals, causes of graft loss, and of patient death were similar across time. CONCLUSION: The unfavorable tendency in the quality of cadaveric donors during the last 12 years had no negative impact on graft function and patient outcome.